Toward a Qur’anic philosophy of multicultural education: A hermeneutical and ethical approach - Vambudi, Viky Nur; Sutisna, Asep; Sutomo, Sutomo; AN, Andri Nirwana; Alauddin, Muhammad Badat (Priviet Social Sciences Journal, 2026)
Multicultural education is increasingly important in the context of globalization that affects cultural and religious diversity in society. This research aims to explore the philosophical basis of multicultural education through the interpretation of the Qur'an and the role of hermeneutic approaches in Islamic religious education. The research method uses a Systematic Literature Review based on the Scopus database from 2022 to 2025 by analyzing Scopus-indexed scientific articles related to multiculturalism, Islamic education, and hermeneutics. From the search results, it was found that 229 articles were filtered into 37 relevant articles, and finally 20 articles that met the inclusion criteria were selected for further analysis. The results of the study show that the interpretation of the Qur'an with a contextual hermeneutic approach provides a strong philosophical basis for multicultural education with the values of inclusivity, justice, and respect for diversity. This research also identifies the important contribution of hermeneutics in enriching the interpretation of Qur'anic values that support a more inclusive and tolerant education. The conclusion in this study is that Islamic religious education based on Qur'anic values can create a harmonious and pluralistic society if applied with a more critical and contextual approach. The main contribution of this article is to fill the research gap on the application of Qur'an interpretation in multicultural education and to introduce a broader hermeneutic approach in the context of Islamic religious education in an increasingly diverse society.